Control of Fetal Growth and Neonatal Survival by the RasGAP-Associated Endoribonuclease G3BP - Zekri, Latifa (American Society for Microbiology, 2005)
The regulation of mRNA stability plays a major role in the control of gene expression during cell proliferation, differentiation, and development. Here, we show that inactivation of the RasGAP-associated endoribonuclease (G3BP)-encoding gene leads to embryonic lethality and growth retardation. G3BP(−)(/)(−) mice that survived to term exhibited increased apoptotic cell death in the central nervous system and neonatal lethality. Both in mouse embryonic fibroblasts and during development, the absence of G3BP altered the expression of essential growth factors, among which imprinted gene products and growth arrest-specific mRNAs were outstanding. The results demonstrate that G3BP is essential for proper embryonic growth and development by mediating the coordinate expression of multiple imprinted growth-regulatory transcripts.